2000
DOI: 10.1212/wnl.54.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonconvulsive status epilepticus in comatose patients

Abstract: This large-scale EEG evaluation of comatose patients without clinical signs of seizure activity found that NCSE is an underrecognized cause of coma, occurring in 8% of all comatose patients without signs of seizure activity. EEG should be included in the routine evaluation of comatose patients even if clinical seizure activity is not apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
341
4
30

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(391 citation statements)
references
References 26 publications
12
341
4
30
Order By: Relevance
“…Previous studies have shown that NCS/NCSE is frequently seen with acute brain insults with an incidence ranging between 8 and 48% depending on the patient population studied [1][2][3][4][5][6][7][8]. The etiology of NCS/NCSE in our patient population was comparable to previous reports stemming from both population-based [2] and retrospective studies [38].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that NCS/NCSE is frequently seen with acute brain insults with an incidence ranging between 8 and 48% depending on the patient population studied [1][2][3][4][5][6][7][8]. The etiology of NCS/NCSE in our patient population was comparable to previous reports stemming from both population-based [2] and retrospective studies [38].…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of NCS and NCSE ranges between 8 and 48% depending on the patient population studied [1][2][3][4][5][6][7][8]. The mortality rate of neurologically critically ill patients afflicted with NCSE is 18-57% [9,10] while the presence of NCS is associated with a mortality rate of 33% [10].…”
Section: Introductionmentioning
confidence: 99%
“…We learn from this study that ESz and PEDs are also relatively frequent in critical patients without known primary neurological injury, confirming findings from a previous cohort, which also included some neurological patients [5]. It also indicates that patients with these EEG abnormalities may have worse prognosis.…”
supporting
confidence: 88%
“…The different patterns of EEG obtained in emergency patients, although nonspecific, can often be correlated with the etiology of diseases of the central nervous system such as trauma 4 , vascular injury and anoxic-ischemic injury due to cardiorespiratory arrest 5 . In hepatic encephalopathy 6,7 , Creutzfeldt-Jakob disease 8 , non-convulsive status epilepticus [9][10][11][12][13][14][15] and herpes simplex encephalitis 16 , EEG is decisive for diagnosis and thus guides therapy and gives an indication of the prognosis.…”
mentioning
confidence: 99%